Case Report: Severe Neonatal Course in Paternally Derived Familial Hypocalciuric Hypercalcemia - Höppner, Jakob; Lais, Sabrina; Roll, Claudia; Wegener-Panzer, Andreas; Wieczorek, Dagmar; Högler, Wolfgang; Grasemann, Corinna (Frontiers in Endocrinology, 2021)
Familial hypocalciuric hypercalcemia (FHH, [OMIM #145980]) is recognized as a benign endocrine condition affecting PTH and calcium levels due to heterozygous inactivating mutations in the calcium sensing receptor (CaSR). The condition is often un- or misdiagnosed but may have a prevalence as high as 74 in 100.000. Few reports described transient neonatal hyperparathyroidism. Here, the neonatal courses of two brothers with paternally inherited FHH (CaSR c.554G>A; p.(Arg185Gln)) are described. The older brother was born preterm at 25 weeks gestation with hypercalcemia and hyperparathyroidism. The younger brother, born full-term, had severe hyperparathyroidism, muscular hypotonia, thrombocytopenia, failure to thrive and multiple metaphyseal fractures. Treatment with cinacalcet was initiated, which resulted in subsequent reduction of PTH levels and prompt clinical improvement. While it is known that homozygous mutations in CaSR may lead to life-threatening forms of neonatal severe hyperparathyroidism (NSHPT), few reports have described a severe clinical course in neonates with FHH due to heterozygous mutations. However, based on the pathophysiological framework, in de novo or paternally transmitted FHH the differing calcium needs of mother and fetus can be expected to induce fetal hyperparathyroidism and may result in severe perinatal complications as described in this report. FHH is a mostly benign condition, but transient neonatal hyperparathyroidism may occur in affected neonates when the mutation is paternally inherited. If severe, the condition can be treated successfully with cinacalcet. Patients with FHH should be informed about the risk of neonatal disease manifestation in order to monitor pregnancies and neonates.